Anophthalmus Miroslavae sp. n. iz Slovenije (Coleoptera: Carabidae: Trechinae) - Kofler, Bojan (Acta entomologica slovenica (Ljubljana), 2006)
The geographical distribution and frequency of Anophthalmus alphonsi, an endemic hypogean beetle species from Škofjeloško Hribovje (north-western Slovenia) was studied. A long term search in the classical finding-places and also in newly discovered caves, abysses and shafts in the region was made. The abyss Brezno na Malem Lubniku on Mt. Lubnik, the cave Flančenk near the village Pevno, and the old shafts near the town Železniki are the new findings sites.
Keywords: Coleoptera; hrošči; insekti; zoogeografija